An der Schnittstelle von bildender Kunst und Theater: Eine interdisziplinäre didaktische Annäherung zwischen Theorie und Praxis (Pedagogical Horizons, 2024)
The article addresses the interdisciplinary connection between art and theater education. From the perspective of aesthetic education, the authors attempt to create a meaningful connection between the two fields, which they first develop theoretically and then illustrate using a practical example. The example itself was developed as part of the international Erasmus project ACIIS - Academy for creative, innovative and inclusive schools.